2020
DOI: 10.1021/acs.jpcb.0c01165
|View full text |Cite
|
Sign up to set email alerts
|

Intriguing Intermolecular Interplay in Guanine Quartet Complexes with Alkali and Alkaline Earth Cations

Abstract: The possibility to target noncanonical guanine structures with specific ligands for therapeutic purposes inspired numerous theoretical and experimental investigations of a guanine quartet and its stacked composites. In this work, we employed the interacting quantum atoms methodology to study interactions among different fragments in complexes composed of a guanine quartet and alkali (Li+, Na+, K+) or alkaline earth (Be2+, Mg2+, Ca2+) cations in vacuo: metal–quartet interaction, influence of the cation on guani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 116 publications
0
16
0
Order By: Relevance
“…62 We believe that the instability of Li + -coordinated G-octets originates from the inability of the Li + cation to coordinate all oxygen atoms and subsequently the lack of G-quartet rigidity, which is crucial for G-quartet stacking. In the case of the Mg 2+ cation, the stability might be even more reduced since it was previously shown that G-quartets with earth alkaline cations only exist because of strong cation−guanine attraction 9 and this cation also does not coordinate all oxygen atoms. We will show below that the earth alkaline cations even reduce the strengths of the inner hydrogen bonds in the G-octets relative to those of G-octets coordinated with alkaline cations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…62 We believe that the instability of Li + -coordinated G-octets originates from the inability of the Li + cation to coordinate all oxygen atoms and subsequently the lack of G-quartet rigidity, which is crucial for G-quartet stacking. In the case of the Mg 2+ cation, the stability might be even more reduced since it was previously shown that G-quartets with earth alkaline cations only exist because of strong cation−guanine attraction 9 and this cation also does not coordinate all oxygen atoms. We will show below that the earth alkaline cations even reduce the strengths of the inner hydrogen bonds in the G-octets relative to those of G-octets coordinated with alkaline cations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although the latter interaction is dominated by electrostatics, 6,9 it also has a partially covalent nature. Selected geometrical parameters related to these interactions are collected in Table 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All quantum chemical calculations were performed at the M06-2X/6-311++G(d,p) level 42–47 with the Gaussian program package 48 using an ultrafine integration grid. It has been demonstrated that M06-2X functional successfully describes charged particles, 36,49,50 but also systems with various types of interactions. 31,39,51–57 IQA analysis was performed with the AIMAll software 58 by employing the promega5 basin integration method.…”
Section: Computational Detailsmentioning
confidence: 99%
“…For this purpose, the Interacting Quantum Atoms methodology 21,22 (IQA) was employed, which has so far been successfully utilized for analysis of diverse systems, properties and processes. 23–41 It enables quantification of classical and non-classical interaction terms among selected fragments (the fragments being BN & PCH + , BN & H + , PC & H + , or BN & H + & PC), but also energetical properties of the fragments themselves when their geometry and the environment modify upon reaction advancement. The paper is organized as follows: Section 2 contains details of the computational procedure; the results and their discussion are presented in Section 3; the conclusions are summarized in Section 4.…”
Section: Introductionmentioning
confidence: 99%